A NOVEL TAUOPATHY PRESENTING WITH A MOTOR NEURONE DISEASE PHENOTYPE. Issue 11 (9th October 2013) - Tallantyre, Emma; Wills, Adrian; Revesz, Tamas; Lowe, James
Abstract : We report a case of subacute progressive walking difficulty, dysarthria and dysphagia, which clinically resembled motor neurone disease (MND) but which proved on post mortem examination to be a novel tauopathy with characteristic globular glial inclusions. A 79 year old man was admitted to hospital following a fall. There was a background history of progressive walking difficulty over a period of six months, a three month history of slurred speech and a two week history of difficulty swallowing. There was no family history of neurological disease. His sister thought he had shown gradual deterioration in memory over the previous four to six months. On examination there was evidence of neuromuscular respiratory failure, right basal consolidation and pseudobulbar palsy. Fasciculations, wasting and weakness were present in all four limbs but reflexes were brisk. There were no extrapyramidal signs. Despite supportive treatment the patient deteriorated and died 12 days after admission. A post mortem examination revealed widespread tau pathology including astrocytic plaque reminiscent of corticobasal degeneration, tufted–like astrocytes reminiscent of progressive supranuclear palsy and globular oligodendroglial inclusions. Pathology affected the pons, medulla, spinal cord, cerebellum and basal ganglia but the cortex was relatively spared. Cases of MND associated with fronto–temporal dementia (FTD) are almost exclusively associated with TDP–43 pathology. Recently, however, a novel tauopathy has been described which can manifest with a syndrome indistinguishable from MND and/or FTD. The most striking distinguishing feature is the globular morphology of glial and neuronal tau inclusions, hence to term GGT. Patients with GGT tend to present with pyramidal and extrapyramidal features and/or cognitive deficits consistent with the behavioural variant of FTD. Our case was unusual for the absence of extrapyramidal features, the presence of lower motor neurone limb signs and the pathological features of relative cortical sparing and prominent astrocytic tau pathology. This case represents a new variant of Globular Glial Tauopathy (GGT) which has not previously been described.